Pengembangan Silamak Pangek Pisang sebagai Makanan Tradisional Unggulan Nagari Kinari melalui Rekayasa Proses dan Modifikasi Bentuk - Kurnia Harlina Dewi; Risa Meutia; Nika Rahma Yanti; Rahmi Awalina (Warta Pengabdian Andalas, 2020)
Silamak Pangek Pisang is, made of banana fruit, one of the Nagari Kinari Traditional Foods that has the potential to be developed and introduced to the commercial world. The development of Silamak Pangek Pisang as traditional food is expected to be able to be an effort to increase family income. Therefore, it is necessary to transfer a technology and product development, so that these traditional food products and traditional foods can be accepted by many walks of life outside Nagari Kinari. Efforts can be made in developing traditional food products are modification of forms and processes. Form engineering is done by making Silamak Pangek Pisang that easier to consume with better appearance. While the process modification is done to make the Silamak Pangek Pisang less susceptible to damaged. The results show, a transfer of technology occurred where development of traditional food products create a more attractive appearance, and simpler to pack, consumed, with prolonged shelf life.